(untitled) (NAU Journal of Technology and Vocational Education, 2026)
The study examined the role of entrepreneurship engagement on the improvement of OTM students’ standard of living. It was guided by three research questions. A descriptive survey research design was used. The population comprised all Business education postgraduate students in Tai Solarin University of Education, Ijagun, Ogun State, Nigeria. A total of 75 Business education postgraduate students were selected as sample size of the study. Purposive and stratified sampling technique was adopted for the selection of the sample size. Researcher instrument tagged; Entrepreneurship Engagement and Living Standard Questionnaire (EELSQ) with 0.83 reliability coefficient was used for data collection. reported. Descriptive statistics were used for answering research questions 1 and 2. Research question 3 was answered using PPMC. The findings of the study revealed that lack of access to funding, poor infrastructure, corruption, limited access to markets and poor infrastructural development were among issues facing entrepreneurship engagement. Improvement in income, improvement in work engagement, enhance job creation, reduces unemployment and increases economic productivity were among the benefits of entrepreneurship engagement for improvement of OTM living standard. There was relationship between the independent variable and the dependent variable (standard of living) in the order of (r = 0.390, p < .05). The study recommends among other things that stakeholders of institutions should provide adequate funds, easy access to markets and develop infrastructural facilities of institutions in other to improve the entrepreneurship engagement of students’ together with their living standard.